Acute traumatic coagulopathy: new concepts in endotheliopathy and hemostatic resuscitation - Ana Clara Pessoa Pontes; João Francisco Ferreira Andriola; Gabriel Alves Groff; Carla Lúcia de Camargo; Elisângela da Silva Mendes Nunes; Paulo Rogério Vieira Lamarca Flores (International Health Sciences Review, 2026)
Acute traumatic coagulopathy (ATC) is an early and complex manifestation of trauma-induced coagulopathy that develops through the interaction of hemorrhagic shock, tissue hypoperfusion, endothelial dysfunction, glycocalyx degradation, inflammation, and dysregulated fibrinolysis, contributing substantially to preventable trauma-related mortality. This narrative review aimed to summarize current evidence regarding the pathophysiological mechanisms underlying ATC, with emphasis on trauma-induced endotheliopathy, and to discuss contemporary strategies for diagnosis, monitoring, and hemostatic resuscitation in both prehospital and in-hospital settings. A literature search was conducted in PubMed/MEDLINE, the Virtual Health Library, SciELO, and the CAPES Journal Portal, complemented by international clinical guidelines and expert consensus documents, prioritizing recent studies while including landmark publications when appropriate. Current evidence demonstrates that ATC extends beyond traditional concepts of dilutional coagulopathy, involving endothelial injury, glycocalyx disruption, platelet dysfunction, fibrinogen depletion, and heterogeneous fibrinolytic phenotypes. Early recognition, rapid hemorrhage control, balanced transfusion strategies, tranexamic acid administration, correction of hypocalcemia, and the use of viscoelastic assays have become central components of modern hemostatic resuscitation. Advances in understanding the interplay between endotheliopathy and coagulation have transformed the management of severe trauma, supporting an individualized, physiology-guided approach that may improve hemostatic control and clinical outcomes.